ANALISIS YURIDIS TERHADAP HAK PREROGATIF PRESIDEN SEBELUM DAN SESUDAH AMANDEMEN UNDANG-UNDANG DASAR 1945 - M JAMHURI; Dodi Haryono; Abdul Ghafur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Amendment Act of 1945 that occurred in the era of reform based on a commitment to reinforce the Presidential system. Instead, the powers of the President as head of state seems limited by the meddling of other state institutions such as parliament, it weakens the system as the prerogative of the presidency itself. Prerogative is one muntlak rights owned by the President as head of state. Practice of the presidency in Indonesia established since 18 August 1945, Indonesian has a constitution which became the basis for a set of government (1945) and the presidency, which led the entire nation. In fact, the prerogative established in the Act of 1945 reduced that the institution of Parliament who are members of the prerogative of the President. Therefore, this study aimed to understand the prerogative of the president in Indonesia in the reform era at once formulate implications for the executive and legislative relations and the implementation of the ideal. This type of research can be can be classified into types of normative juridical research, because it makes the literature as the main focus. Source of data used, the primary legal materials, secondary law, and tertiary legal materials. Data collection techniques in this study using the method of literature study.The results showed that the application of the prerogative of the President in a presidential system of government actually weaken the presidential system and have implications for the executive and legislative relations. Some of the things that the implications are; First, the number of political interests. Second, the absence of regulation of the relationship between state institutions. Third, the weak position of the President as head of state. Prinip ideally application prerogative of the President, in order to create stability prerogative of the President of Indonesia, there are several things that need to be addressed within the prerogative of the President of our system, namely: First, setting the relationship between state institutions, second, does not always have to associate with politics, and Third, strengthening the institutional design of the presidency. The author suggests needed muntlak its prerogatives defined by the rules of law more clearly so that it will produce a strong and efficient government and the effort to strengthen the position of President of the institution of the presidency that is not weak against the Parliament, by way of separation institution of the presidency of the Council of Representatives (DPR) and the prerogative of the President through the rules of the Act are clear.Keywords: President, prerogatives, before, after amendment